2019
DOI: 10.17245/jdapm.2019.19.6.369
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the effectiveness of a mobile app (Little Lovely Dentist) and the tell-show-do technique in the management of dental anxiety and fear: a randomized controlled trial

Abstract: Background: Behavior guidance is a technique used to subdue inappropriate behavior by establishing communication that meets the needs of a child. This study aimed to measure the effectiveness of a mobile app (Little Lovely Dentist) compared to the tell-show-do (TSD) technique in managing anxious children during their first dental visit. Methods: Fifty children (30 boys and 20 girls) without any past dental experience, aged from 7 to 11 years, were randomly allocated into either the dental app group or the TSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
3
16
1
6
Order By: Relevance
“…This study was carried out from August 2020 till December 2020 in the department of paediatric dentistry at Altamash Institute of Dental Medicine, Pakistan. OpenEpi® software was used to calculate the sample size by keeping a 95% confidence interval and the desired percentile of 50% [16]. The estimated sample size was 40 patients per group.…”
Section: Study Setting and Samplementioning
confidence: 99%
“…This study was carried out from August 2020 till December 2020 in the department of paediatric dentistry at Altamash Institute of Dental Medicine, Pakistan. OpenEpi® software was used to calculate the sample size by keeping a 95% confidence interval and the desired percentile of 50% [16]. The estimated sample size was 40 patients per group.…”
Section: Study Setting and Samplementioning
confidence: 99%
“…Elicherla et al ( 2019 ) evaluated the comparative effectiveness of a mobile app (Little Lovely Dentist) and the TSD technique in managing dental anxiety and fear. Fifty 7–11 years old children were randomly allocated into the dental app group or the TSD group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Elicherla et al compared the effectiveness of a smartphone application (Little Lovely Dentist) with the tell-show-do (TSD) technique in reducing the dental anxiety during first visits. They found that children educated using the application prior to their dental visits had significantly lower anxiety levels compared with the TSD group [38].…”
Section: Discussionmentioning
confidence: 99%